PENGARUH PROFESIONALITAS, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA(STUDI KASUS PADA SATUAN INTELKAM POLRESTA BANDAR LAMPUNG) - Fajar Chema Agira; Habiburahman Habiburahman; Haninun Haninun (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study seeks to examine and evaluate the impact of professionalism, work discipline, and work motivation on employee performance within the Intelligence and Security Unit of the Bandar Lampung Police. This research adopts a quantitative approach. A saturated sampling technique was applied, involving the entire population as the research sample, consisting of 60 respondents. Data were analyzed using classical assumption tests, multiple regression analysis, and hypothesis testing. The findings indicate that professionalism, work discipline, and work motivation significantly affect performance both partially and simultaneously among members of the Intelligence and Security Unit of the Bandar Lampung Police. Collectively, these variables account for 89.1% of the variance in performance, while the remaining 10.9% is explained by other factors not included in this study.